State Policy of Consumer Protection in the Digital Financial Services Market in Ukraine - Lobozynska, Sophia; Skomorovych, Iryna; Vladychyn, Ulyana (Journal of Finance and Financial Law, 2020)
The rapid development of digital financial technologies in Ukraine leads to the emergence of new risks and to significant consumers’ losses in the financial market. The aim of the study is to develop strategic directions of state policy of consumer protection in the digital financial services market considering the best world practices and features of the financial system of Ukraine.System scientific analysis was used to study the possibilities of implementing international quality standards for digital financial services in Ukrainian legislation. The method of statistical analysis of data was used to form the imperial basis of the study.Based on the global experience and taking into account the peculiarities of Ukrainian fintech market the state policy should consist of three strategic directions: 1) create a system of legal regulation of the mechanism of protection of consumers’ rights of digital financial services; 2)introducing a risk-oriented approach to regulating the digital financial services delivery processto consumers; 3) strengthening of digital financial literacy and public awareness. Such state policy will form a reliable system of consumer protection in the digital services market in Ukraine.